The CIA & Congress : the untold story from Truman to Kennedy - Barrett, David M., 1951- (Lawrence, Kan. : University Press of Kansas, 2005)
"Drawing on a wealth of newly declassified documents, research at some two dozen archives, and interviews with former officials, David M.
Barrett provides an unprecedented and often colorful account of relations between American spymasters and Capitol Hill. He chronicles the CIA's dealings with senior legislators who were haunted by memories of our intelligence failure at Pearl Harbor and yet riddled with fears that such an organization might morph into an American Gestapo.
He focuses in particular on the efforts of Congress to monitor, finance, and control the agency's activities from the creation of the national security state in 1947 through the planning for the ill-fated Bay of Pigs invasion in 1961."
"The CIA and Congress provides a much-needed historical perspective for current debates in Congress and beyond concerning the agency's recent failures and ultimate fate.
In our post-9/11 era, it shows that anxieties over the challenges to democracy posed by our intelligence communities have been with us from the very beginning."--Jacket.
pt. 1. The Truman era, 1947-1952. No "American Gestapo," but "No more Pearl Harbors"-- Initial oversight: budgets and covert action -- "A South American Pearl Harbor" -- "This Is an Espionage Bill" -- The Soviet A-bomb: "We apparently don't have the remotest idea" -- Communists and "perverts" in the CIA -- Korea: "No better today than on December 7, 1941" -- A new DCI -- The "dirty business" -- Portraits -- CIA subcommittees, intelligence roles, and budgets -- "We don't let just anybody look at our files" -- "There will be no changes" -- pt. 2. The Eisenhower era, 1953-1960. Meddling? -- Getting "Taberized" -- Guatemala: sterilizing a "red infection" -- Mr. Mansfield goes to the Senate -- Joseph McCarthy: the CIA's other would-be overseer -- "You, who championed our cause" -- Barons restored -- "Dodging dead cats" -- "They have to have a building" -- The new Mansfield resolution: two surprises -- "We have a history of underestimation" -- Hungary and the Suez: "We had a very good idea, Senator" -- Sputnik -- An early "year of intelligence"? -- "I cannot always predict when there is going to be a riot" -- Iraq: "Our intelligence was just plain lousy" -- Return to Missile Gap -- From the Pforzheimer era to the Warner era -- Subordinating intelligence? -- In and out of hearing rooms -- "Who are our liquidators?" -- "I'd like to tell him to his face what I think about him" -- U-2: "We have felt these operations were appropriate" -- Pouring oil on fire -- "Their answer to that demand": Congressional paternity? -- "My opinion of the CIA went skyrocketing" -- pt. 3. Cuba, the CIA, and Congress: 1960-1961. Castro: "This fellow is bad and ought to go" -- "What is the rationale behind that?" -- "I agree that you had to replace Dulles" -- Afterword: alarms.
Includes bibliographical references (pages 511-519) and index.
Keywords: United States. -- Central Intelligence Agency -- History; United States. -- Congress; United States -- Foreign relations -- 1945-1989.; United States. -- Central Intelligence Agency. -- History; Central Intelligence Agency -- Histoire; Congress; 1945-1989.; 15.85 history of America; HISTORY / United States / 20th Century; POLITICAL SCIENCE / American Government / Legislative Branch; POLITICAL SCIENCE / Intelligence & Espionage; United States. -- Central Intelligence Agency; United States. -- Congress; Diplomatic relations; United States; USA -- Congress; USA -- Central Intelligence Agency; CIA; The Congress; Foreign policy; United States; 1945-1989; 1945-1950; 1950-2000; History